Overview of COVID-19 Test Results (2021–2022) at the Laboratory of the Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Febrianti, Fitri Ayu; Khasanah, Uswatun; Weni, Mustika (GHMJ (Global Health Management Journal), 2024)
Background: COVID-19 (Coronavirus Disease-19) is a respiratory infection caused by the SARS-CoV-2 virus. In 2020, the World Health Organization (WHO) declared COVID-19 a global pandemic due to the rapid rise in cases and mortality rates worldwide. The pandemic has impacted millions of people and continues to pose a significant global public health threat. Accurate diagnosis of the disease depends on laboratory testing, with RT-PCR widely recognized as the gold standard for confirming COVID-19. Aims: To describe an overview of COVID-19 test results at Laboratory Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia, from 2021-2022. Methods: This study used a descriptive observational method. The sample was collected in July 2024 using a total sampling technique. The sample includes all 135,713 patients who had COVID-19 tests at Laboratory Faculty of Medicine Swadaya Gunung Jati Univesity between 2021 and 2022. Data were collected from medical records of COVID-19 test. The variables of this study include gender, age, and COVID-19 test results. A statistical analysis was used to determine frequency distribution. Results: The results of the study showed that among the sample who tested for COVID-19, the majority are male (50.9%) and early adolescent age group (23.9%). RT-PCR test findings were positive in 16.3% of patients and negative in 83.7% of patients. Among PCR positive cases, the majority are female (17.4%), with seniors age groups >65 years accounting for 39.0%. Conclusion: Most of the tested samples are males and early adolescent age groups, with more negative PCR results than positive ones. Among positive cases, the highest number was found in females and seniors age group. It is recommended that females and seniors age groups keep protected during COVID-19 outbreaks. Received: 25 September 2024  |  Reviewed: 22 October 2024  |  Revised: 30 November 2024  |  Accepted: 11 December 2024.